An electrochromic material, its preparation method and applications

By using modified polyionic liquids and crosslinking agents to regulate the electrostatic interaction between anions and cations, and combining this with metal-inorganic salt exchange, the self-aggregation problem of viologen-based electrochromic materials was solved, improving the color-changing speed and adhesion of the device, and enhancing the overall performance of the electrochromic device.

CN119613906BActive Publication Date: 2025-11-14NINGBO LICON OPTOELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411736494.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-11-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The introduction of polyionic liquids causes viologen-based electrochromic materials to generate self-aggregates during redox reactions, resulting in decreased device performance, slow color change rate, and poor adhesion to the substrate.

Method used

Modified polyionic liquids are used. By introducing imidazole cationic PIL polymers with flexible alkoxy side groups and crosslinking agents, the electrostatic interaction between anions and cations is regulated. Combined with metal inorganic salts as an anion exchange medium, the flexibility and adhesion of the material are improved, and the generation of self-aggregates is suppressed.

Benefits of technology

It effectively inhibits the formation of self-aggregates in viologen-based electrochromic materials, improves the physical properties and adhesion of devices, and enhances the color-changing speed and overall performance of devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

This invention discloses an electrochromic material, its preparation method, and its applications. The raw materials of the electrochromic material mainly include modified polyionic liquid, ethyl viologen diiodide, ferrocene, crosslinking agent, and other additives. The main component of the modified polyionic liquid includes an imidazole cationic PIL polymer with flexible alkoxy side groups. The general formula of the imidazole cationic PIL polymer with flexible alkoxy side groups is PIL-m-TFSI and PIL-2-x. This invention solves the problem of suppressing the formation of dimers in viologen-based electrochromic materials by introducing polyionic liquids, thereby improving device performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochromic materials technology, specifically to an electrochromic material, its preparation method, and its applications. Background Technology

[0002] Electrochromic technology offers energy savings while providing convenience and enhanced safety for travelers, leading to its widespread application in electrochemical fields such as aircraft windows, automotive anti-glare rearview mirrors, microdisplays, and sensors. The synthesis and application of electrochromic materials are currently a research hotspot. Viologen, as a color-changing material, is a widely studied and mature organic small molecule material with excellent redox reversibility, capable of changing color under the influence of external light, electricity, heat, and chemicals. However, viologen undergoes side reactions during redox reactions, such as self-polymerization to form viologen free radical dimers.

[0003] Current research has found that the introduction of polyionic liquids can suppress the formation of dimers in viologen-based electrochromic materials, thereby improving device performance. One approach is to directly add polyionic liquids to form blended electrolytes to improve electrochromic device performance; however, imidazole-based polyionic liquids are inherently brittle and difficult to form films, making them unsuitable as electrolytes for preparing all-solid-state and flexible electrochromic devices. Another approach involves copolymerizing ionic liquid monomers with viologen-based electrochromic materials to form functional polymer electrolytes that serve as ionic conductors and matrices; however, copolymerizing ionic liquid monomers with viologen-based electrochromic materials leads to problems such as slow color-changing speed and poor adhesion to the substrate.

[0004] In order to address the issue of suppressing the formation of dimers in viologen-based electrochromic materials by introducing polyionic liquids, thereby improving device performance, the present invention proposes the following solution. Summary of the Invention

[0005] This application provides an electrochromic material, its preparation method, and its application, which addresses the problem of suppressing the formation of dimers in viologen-based electrochromic materials by introducing polyionic liquids, thereby improving device performance.

[0006] This application provides an electrochromic material, the raw materials of which mainly include modified polyionic liquid, ethyl viologen diiodide, ferrocene, crosslinking agent, and other additives; the main component of the modified polyionic liquid includes an imidazole cationic PIL polymer with flexible alkoxy side groups; the general formula of the imidazole cationic PIL polymer with flexible alkoxy side groups is PIL-m-TFSI, and its specific structure is as follows:

[0007] ;

[0008] And PIL-2-x, the specific structure is as follows:

[0009] .

[0010] By adopting the above technical solution, the main component of the modified polyionic liquid in this application includes an imidazole cationic PIL polymer with flexible alkoxy side groups. The introduction of alkoxy groups can effectively regulate the phase transition temperature and viscoelastic behavior of the PIL by affecting the electrostatic interaction strength between anions and cations. Furthermore, through the synergistic effect of hydrogen bonding and electrostatic interactions, it helps to solve the problems of flexibility and macroscopic adhesion, not only suppressing the formation of dimers in viologen-based electrochromic materials but also significantly improving the physical performance of electrochromic devices.

[0011] Preferably, in the structural formula of the PIL-m-TFSI, R m The structural formula is

[0012] ;

[0013] ;

[0014] One of them; m=1,2,3.

[0015] By adopting the above technical solution, the R used in the embodiments of this application m Halogenated hydrocarbons with groups R m All of them are long chains with alkoxy groups, which helps to regulate the phase transition temperature and viscoelastic behavior of PILs. Furthermore, the introduction of alkoxy groups through quaternization reactions via halogenated hydrocarbons can improve the yield of alkoxy ionic liquids.

[0016] Preferably, in the structural formula of PIL-2-x, x is

[0017] ;

[0018] ;

[0019] One of them.

[0020] By adopting the above technical solution, which includes metal inorganic salts with x-groups, and using them as anion exchangers, the synergistic effect of electrochromic material and ITO conductive glass electrostatic interaction is improved, thereby improving the physical performance of electrochromic devices.

[0021] Preferably, the crosslinking agent includes one or more combinations of 1,6-dibromohexane, 1-bromoheptane, and 1-bromobutane.

[0022] By adopting the above technical solution, 1,6-dibromohexane, 1-bromoheptane, and 1-bromobutane can be used as crosslinking agents to increase the solubility and transparency of polyionic liquids, thereby increasing the flexibility and film-forming properties of polyionic liquids through blending and stirring.

[0023] On the other hand, this application discloses a method for preparing an electrochromic material, including the following steps: synthesis of modified polyionic liquid and preparation of electrochromic material.

[0024] Preferably, the synthesis of the modified polyionic liquid includes the following steps: S1, quaternization reaction: weigh a certain mass of the liquid containing R m S1. Halogenated hydrocarbons of the group and a certain mass of N-vinylimidazolium are dissolved together in DMSO. The mixture is stirred continuously at a certain temperature and a certain amount of ethyl acetate is added. The product is precipitated in the form of a precipitate, and then extracted, washed and vacuum dried with ethyl acetate and water to finally obtain the alkoxy IL monomer; S2. Free radical polymerization reaction: The alkoxy IL monomer is dissolved in DMSO, a certain amount of initiator is added, and the mixture is stirred continuously at a certain temperature for a certain time. Ethyl acetate is added, and the product is precipitated in the form of a precipitate. After multiple washing and vacuum drying, the alkoxy-functionalized PIL-m-Cl is obtained; S3. Ion exchange reaction: The alkoxy-functionalized PIL-m-Cl is dissolved in deionized water to obtain solution A. The metal inorganic salt with the x group is dissolved in deionized water to obtain solution B. Solution A and solution B are mixed, and the precipitate is collected, extracted and washed with ethyl acetate and water, and then vacuum dried to finally obtain the modified polyionic liquid.

[0025] Preferably, the haloalkane with the Rm group includes one of 2-chloroethyl ether, 1-chloro-2-(2-ethoxyethoxy)ethane, and 1-(2-chloroethoxy)-2-(2-methoxyethoxy)ethane.

[0026] Preferably, the metal inorganic salt of the x group includes one of LiTFSI, LiBF4, and LiPF6.

[0027] Preferably, the preparation of the electrochromic material includes the following steps: adding the modified polyionic liquid to a certain amount of ethanol and stirring for a certain time, adding a crosslinking agent according to a certain ratio and heating and stirring, then adding ethyl viologen diiodide and ferrocene and stirring until completely dissolved to obtain the electrochromic material.

[0028] On the other hand, this application also discloses an application of an electrochromic material, the application of the electrochromic material in an electrochromic device; the electrochromic material is coated on ITO conductive glass, and excess electrolyte and bubbles are extruded by using a combination of an oil-free air compressor and a pneumatic compressor to prepare an electrochromic device.

[0029] One or more technical solutions provided in this application have at least the following technical effects or advantages:

[0030] 1. This application introduces alkoxy groups into the modified polyionic liquid, thereby affecting the electrostatic interaction strength between anions and cations, effectively regulating the phase transition temperature and viscoelastic behavior of the PIL. In turn, under the synergistic effect of hydrogen bonding and electrostatic interaction, it helps to solve the problems of flexibility and macroscopic adhesion. It not only inhibits the generation of dimers in viologen-based electrochromic materials, but also greatly improves the physical performance of electrochromic devices.

[0031] 2. In this application, R is used in the PIL-m-TFSI structure. m Halogenated hydrocarbons of the group, via R m All of them are long chains with alkoxy groups, which helps to regulate the phase transition temperature and viscoelastic behavior of PILs. Furthermore, the introduction of alkoxy groups through quaternization reactions via halogenated hydrocarbons can improve the yield of alkoxy ionic liquids.

[0032] 3. This application uses an inorganic metal salt with an x-group as an anion exchange medium to promote the ion exchange reaction, enhance the synergistic effect of electrochromic material and ITO conductive glass electrostatic interaction, and thus improve the physical performance of electrochromic device. Detailed Implementation

[0033] This application provides an electrochromic material, its preparation method, and its application, which addresses the problem of suppressing the formation of dimers in viologen-based electrochromic materials by introducing polyionic liquids, thereby improving device performance.

[0034] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0035] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of this application described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion; for example, a process, method, system, product, or server that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or modules not explicitly listed or inherent to such processes, methods, products, or devices.

[0036] raw material

[0037] 2-Chloroethyl ethyl ether CAS No.: 628-34-2 Molecular weight: 108.567 Purity >98%;

[0038] 1-Chloro-2-(2-ethoxyethoxy)ethane CAS No.: 41771-35-1 Molecular weight: 152.62 Purity >95%;

[0039] 1-(2-Chloroethoxy)-2-(2-Methoxyethoxy)ethane CAS No.: 52995-76-3 Molecular weight: 182.65 Purity >95%;

[0040] LiTFSI (Lithium Bis(trifluoromethanesulfonyl)imide) CAS No.: 90076-65-6 Molecular Weight: 287.087 Purity: 99%;

[0041] LiBF4 CAS No.: 14283-07-9 Molecular Weight: 93.746 Purity: 99%

[0042] LiPF6 CAS No.: 21324-40-3 Molecular Weight: 151.905 Purity: 99%

[0043] N-Vinylimidazolium CAS No.: 1072-63-5 Molecular Weight: 94.115 Purity: 99%

[0044] 1,6-Dibromohexane CAS No.: 629-03-8 Molecular weight: 243.967 Purity: 99%;

[0045] 1-Bromoheptane CAS No.: 629-04-9 Molecular weight: 179.098 Purity: 99%;

[0046] 1-Bromobutane CAS No.: 109-65-9 Molecular Weight: 137.018 Purity: 99%;

[0047] Ethyl viologen diiodide CAS No.: 1983-61-5 Molecular weight: 468.115 Purity: 97%;

[0048] Ferrocene CAS No.: 102-54-5 Molecular Weight: 186.031 Purity: 99% Example 1

[0049] S1. Quaternization reaction: Weigh 1.0 kg of 2-chloroethyl ether and 0.8 kg of N-vinylimidazole and dissolve them together in 1.2 L of dimethyl sulfoxide solution (DMSO). Stir the mixture continuously at 95 °C for 48 h. After the solution cools to room temperature, add an appropriate amount of ethyl acetate to precipitate the product. Extract, wash and vacuum dry the product with ethyl acetate and water to finally obtain the alkoxy IL monomer.

[0050] S2. Free radical polymerization reaction: The alkoxy IL monomer prepared above was dissolved in 1.0 L of dimethyl sulfoxide solution (DMSO), 50 g of initiator azobisisobutyronitrile (AIBN) was added, and the reaction was stirred continuously at 70 °C for 24 h. An appropriate amount of ethyl acetate was added, and the product was precipitated in the form of a precipitate. After washing and vacuum drying multiple times, alkoxy-functionalized PIL-m-Cl was obtained. In this example, m=1, that is, PIL-1-Cl was obtained.

[0051] S3. Ion exchange reaction: 0.5 kg of alkoxy-functionalized PIL-1-Cl was dissolved in 0.8 L of deionized water to obtain solution A. 1.6 kg of LiTFSI (lithium bis(trifluoromethanesulfonylimide)) metal inorganic salt was dissolved in 1.0 L of deionized water to obtain solution B. Solution A and solution B were mixed and stirred at room temperature for 48 h. The precipitate was collected, extracted and washed with ethyl acetate and water, and then dried under vacuum to finally obtain the modified polyionic liquid.

[0052] S4. Preparation of electrochromic material: 0.6 kg of modified polyionic liquid was added to 1.2 L of 95% ethanol and stirred for 24 h. Then, 0.4 kg of 1,6-dibromohexane was added according to the ratio and heated and stirred for 3 h. Then, 0.5 kg of ethyl viologen diiodide and 0.8 kg of ferrocene were added and stirred until completely dissolved to obtain electrochromic material.

[0053] S5. Preparation of electrochromic device: Electrochromic material is coated on two pieces of ITO conductive glass, and excess electrolyte and bubbles are squeezed out of the two pieces of ITO conductive glass by using an oil-free air compressor and a pneumatic press to prepare an electrochromic device. Example 2

[0054] The difference between Example 2 and Example 1 is that, in the S1 quaternization reaction step, R is included. m The halogenated hydrocarbon of the group is 1-chloro-2-(2-ethoxyethoxy)ethane. Example 3

[0055] The difference between Example 3 and Example 1 is that, in the S1 quaternization reaction step, R is included. m The halogenated hydrocarbon of the group is 1-(2-chloroethoxy)-2-(2-methoxyethoxy)ethane. Example 4

[0056] The difference between Example 4 and Example 1 is that, in the S3 ion exchange reaction step, the metal inorganic salt with the x group is lithium tetrafluoroborate (LiBF4). Example 5

[0057] The difference between Example 5 and Example 1 is that, in the S3 ion exchange reaction step, the metal inorganic salt with the x group is lithium hexafluorophosphate (LiPF6).

[0058] Comparative Example 1

[0059] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, N-vinylimidazolium monomer and butyl acrylate were dissolved in anhydrous ethanol, and then copolymerized in anhydrous ethanol using azobisisobutyronitrile (AIBN) as an initiator to obtain a polyionic liquid. This liquid was then crosslinked with 1,6-dibromohexane and reacted with ethyl viologen diiodide to obtain the electrolyte of the polyionic liquid. This electrolyte was then coated onto ITO conductive glass to fabricate an electrochromic device. In this overall preparation process, no alkoxy groups were introduced into the synthesis of the polyionic liquid. Comparative Example 2

[0060] The difference between Comparative Example 1 and Example 1 is that LiTFSI (lithium bis(trifluoromethanesulfonylimide)) and other metal inorganic salts with x groups were not used for ion exchange in the ion exchange reaction step.

[0061] Performance testing experiment

[0062] The electrochromic devices prepared in Examples 1-5 and Comparative Examples 1-2 were used as samples.

[0063] 1. Visual Inspection of Appearance and Dimensions: Testing was conducted according to the national standard JC / T 2631-2021 "Electrochromic Glass". Visual observation was performed at a distance of 600m from the sample, and any visible defects were recorded. The size of point defects and the width of linear defects were measured using a 0.01mm graduation microscope. The length of linear defects was measured using a steel ruler with a 1mm graduation or a measuring instrument of equivalent precision. Point defects included pinholes, bubbles, and optical distortion points; linear defects included dark channels, surface scratches, and glass surface scratches. This application classifies defects into grades based on their severity, from non-destructive to severe: I, II, III, IV, and V. Grade V indicates that the test did not meet the applicable standard.

[0064] 2. Optical Conversion Time Test: The test was conducted according to the national standard JC / T 2631-2021 "Electrochromic Glass" with a sample size of 510mm x 360mm. The length and width of the discoloration area of ​​the sample were measured and recorded. The transmittance at a wavelength of 550nm was used to cyclically control the sample, and the fading conversion time t was calculated based on the experiment. t .

[0065] 3. Optical performance deviation test: The test shall be conducted in accordance with the national standard JC / T 2631-2021 "Electrochromic Glass" test standard. When measuring the color difference of a single piece, take one sample at random and measure the color difference of a single piece at 5 measurement points, and also measure at the other 2 points of the 5 samples. The back of the measured position should be padded with black velvet cloth to maintain the consistency of the background. In addition, the color difference value shall be measured in accordance with the corresponding method specified in GB / T 18915.1, and the permissible deviation index of visible light transmittance in the colored state and the faded state shall be calculated.

[0066] 4. Temperature and Humidity Durability Test: The test is conducted according to the national standard JC / T 2631-2021 "Electrochromic Glass". The sample is placed in a constant temperature chamber, the chamber is turned on, the electrochromic control system is connected and adjusted, and the chamber is cooled to -20℃. After maintaining this temperature for 30 minutes, a cycle begins. One cycle consists of the sample changing from a faded state to a colored state and then back to a faded state. This cycle is performed continuously without interruption until 2000 cycles are reached. The appearance of the sample is observed according to the method used in section 1, Dimensional Inspection. If the appearance does not meet the testing standards, the test is terminated, and the number of cycles is recorded. If no obvious defects are found, the test continues until the final standard is not met. The final number of cycles and cycle time are then obtained.

[0067] 5. Radiation Durability Test: The test is conducted according to the national standard JC / T 2631-2021 "Electrochromic Glass". The sample is placed in the irradiation chamber, the chamber is turned on, and the electrochromic control system is connected and adjusted. During the test, the surface temperature of the sample should be maintained at (65±7)℃. Cyclic cycles begin, with each cycle consisting of the sample changing from a faded state to a colored state and back to a faded state. These cycles are performed continuously without interruption, and the number of cycles is recorded. The cycle is paused after 5000 cycles. The sample is removed and stored at room temperature for at least 1 hour. The optical conversion time is then tested to see if the allowable conversion time is reached. If the test standard is not met, the test is terminated. If the requirements are met, the test continues until the standard is no longer met. The final number of cycles is then obtained.

[0068] Table 1. Performance tests of Examples 1-5 and Comparative Examples 1-2

[0069]

[0070] Based on the experimental data analysis in Table 1, Comparative Example 1 demonstrates the existing technology for preparing electrochromic materials and devices. It involves dissolving N-vinylimidazolium monomer and butyl acrylate in anhydrous ethanol, followed by copolymerization with azobisisobutyronitrile (AIBN) as an initiator in anhydrous ethanol to obtain a polyionic liquid. This liquid is then crosslinked with 1,6-dibromohexane and reacted with ethyl viologen diiodide to obtain the electrolyte, which is then coated onto ITO conductive glass to fabricate an electrochromic device. Under normal operating conditions, the diameter of pinholes, bubbles, and optical distortion points is less than 1.0 mm, and the electrochromic device exhibits no linear defects such as dark channels, film scratches, or glass surface scratches; it belongs to Level I. The optical performance deviation test shows a deviation of ±2%, which is within the normal range of the national standard, but slightly inferior to Examples 1-5.

[0071] Furthermore, in the optical conversion time test, the conversion time of the electrochromic device is divided into coloring conversion time and fading conversion time. The national standard stipulates that the coloring conversion time should not exceed 760s, and the fading conversion time should not exceed 700s. The data from Examples 1-5 and Comparative Example 1 all meet the standard, with Examples 1-5 showing better conversion time than the Comparative Example. Therefore, the experiment demonstrates that the copolymerization of the polyionic liquid and viologen color-changing material in this application can solve the problem of slow color-changing speed in electrochromic devices, thereby effectively improving the performance of the electrochromic material.

[0072] In addition, in the temperature and humidity durability test, Comparative Example 1 showed defects in appearance after 12,000 cycles. These defects included poor substrate adhesion due to the inhibition of dimer formation in the viologen-based electrochromic material caused by the introduction of the polyionic liquid, leading to defects in the appearance of the electrochromic material during use and consequently reducing its weather resistance. Furthermore, in the radiation durability test, Comparative Example 1's conversion time failed to meet the national standard parameters after 15,000 cycles. Its cycle count was less than that of Examples 1-5. Therefore, it can be concluded that the introduction of alkoxy groups into the modified polyionic liquid in this application not only effectively regulates the viscoelastic behavior of the material, helping to solve the problems of flexibility and macroscopic adhesion, but also improves the optical performance of the electrochromic device by inhibiting the formation of dimers in the viologen-based electrochromic material.

[0073] In Comparative Example 2, LiTFSI (lithium bis(trifluoromethanesulfonylimide)) and other metal inorganic salts with x-groups were not used in the ion exchange reaction step. Instead, by using metal inorganic salts as an anion exchange medium, the ion exchange reaction is promoted, enhancing the synergistic effect of the electrochromic material and the ITO conductive glass's electrostatic interaction. Data analysis between Comparative Example 2 and Examples 1-5 shows that, since this application introduces alkoxy groups into the modified polyionic liquid, thereby affecting the electrostatic interaction strength between anions and cations and improving the adhesion between the electrochromic material and the ITO conductive glass, ion exchange with metal inorganic salts containing x-groups is necessary.

[0074] Finally, analysis of Examples 1-5 shows that in the S1 quaternization reaction step, R... m The halogenated hydrocarbon of the group is 1-chloro-2-(2-ethoxyethoxy)ethane; in the S3 ion exchange reaction step, the metal inorganic salt with the x group is LiTFSI (lithium bis(trifluoromethanesulfonylimide)), which can achieve better results, that is, Example 2 is the optimal example.

[0075] It should be noted that the order of the embodiments described above is merely for descriptive purposes and does not represent the superiority or inferiority of the embodiments. Furthermore, specific embodiments have been described above. Other embodiments are within the scope of the appended claims. In some cases, the actions or steps described in the claims can be performed in a different order than those shown in the embodiments and still achieve the desired results. In some implementations, multitasking and parallel processing are also possible or may be advantageous.

[0076] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

[0077] This specification is merely an illustrative description of this application and is intended to cover any and all modifications, variations, combinations, or equivalents within the scope of this application. Clearly, those skilled in the art can make various alterations and modifications to this application without departing from its scope. Therefore, if such modifications and modifications fall within the scope of this application and its equivalents, this application intends to include such modifications and modifications.

Claims

1. An electrochromic material, characterized in that, The raw materials of the color-changing material mainly include modified polyionic liquid, ethyl viologen diiodide, ferrocene, crosslinking agent and other additives; the main component of the modified polyionic liquid is an imidazole cationic PIL polymer with flexible alkoxy side groups; The general formula of the imidazole cationic PIL polymer with flexible alkoxy side groups is PIL-m-TFSI or PIL-2-x, and the specific structure of PIL-m-TFSI is as follows: ; The specific structure of PIL-2-x is as follows: ; In the structural formula of PIL-m-TFSI, R m The structural formula is ; ; One of them; In the structural formula of PIL-2-x, x is... ; One of them; The crosslinking agent is 1,6-dibromohexane.

2. A method for preparing the electrochromic material as described in claim 1, characterized in that, The preparation of the electrochromic material includes the following steps: The modified polyionic liquid was added to a certain amount of ethanol and stirred for a certain time. A crosslinking agent was added according to the proportion and heated and stirred. Then, ethyl viologen diiodide and ferrocene were added and stirred until completely dissolved to obtain an electrochromic material.

3. An application of the electrochromic material as described in claim 1, characterized in that, The electrochromic material is applied to electrochromic devices by coating the electrochromic material onto ITO conductive glass and then extruding excess electrolyte and bubbles using a combination of an oil-free air compressor and a pneumatic compressor to prepare an electrochromic device.

Citation Information

Patent Citations

  • Polyionic liquid adhesive and preparation method thereof

    CN110699020A

  • Electrochromic coating and electrochromic film based on same

    CN115572515A